2019
DOI: 10.1155/2019/9728637
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stabilization of Polyoxymethylene by PEG-Functionalized Hydroxyapatite: Examining the Effects of Reduced Formaldehyde Release and Enhanced Bioactivity

Abstract: Nanostructured hydroxyapatite (HA) functionalized with poly(ethylene glycol) (HA-g-PEG) of different molar mass was used as a thermal stabilizer to prepare polyoxymethylene (POM) composites by a melt processing method. The chemical and crystalline structure of (HA-g-PEG) and POM/HA-g-PEG composites was investigated by means of FTIR and XRD. The thermal properties, degree of crystallinity, and melting behaviour of POM-based composites were analysed with TG, DSC, and TOPEM DSC methods. The tensile strength, Youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…To analyse the thermal stability, thermo gravimetric analysis (TGA) of the three gels were performed at ramping rate of 10 °C/min (Figure a and b). Pielichowska et al have reported that the thermal stability of the material primarily depends on the chemical structure and the molecular weight . Thus, the influence of the length of the alkyl chain in the quaternary and ammonium moiety on the thermal degradation was monitored and the results are depicted in the Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analyse the thermal stability, thermo gravimetric analysis (TGA) of the three gels were performed at ramping rate of 10 °C/min (Figure a and b). Pielichowska et al have reported that the thermal stability of the material primarily depends on the chemical structure and the molecular weight . Thus, the influence of the length of the alkyl chain in the quaternary and ammonium moiety on the thermal degradation was monitored and the results are depicted in the Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The melting and crystallisation behaviour of the as synthesised gels were monitored by Differential scanning calorimetry study (Figure S18). Generally, the thermal property of a material is influenced by the extent of crosslinking . The melting temperature of the crosslinker was observed at 49°C which was associated to the melting of the PEG chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another strategy widely employed to minimize thermal decomposition mechanisms, which do not necessarily sacrifices mechanical properties, is the addition of inorganic nanoparticles such as hydroxyapatite, 3,9,10 clays, [11][12][13] silica, 14 titanium dioxide, 15 zinc oxide, [16][17][18][19][20] zirconium oxide 21 and aluminum oxide. 22,23 Carbonaceous nanoparticles such as graphene oxide (GO) 24 and carbon nanotubes (CNT) 25,26 have also been studied as nanofillers to POM-based systems.…”
Section: Introductionmentioning
confidence: 99%